Biomedical Engineering Lab Manual - Breen, Sarah (Open textbook library., 2023)
The lab manual was written as the second installment that coincides with two lab courses taught at the University of Oklahoma (BME3171, BME3181). These courses are designed to provide Biomedical Engineering students with lab skills and experience in biomedical engineering research and clinical techniques. This manual is used with BME3181 Biomedical Engineering Lab 2 and the following wet lab topics are covered in this lab manual; bioimaging, cell culture, tissue engineering, live-dead and DNA assays.